A 4H-SiC junction barrier Schottky diode with segregated floating trench and super junction. (November 2018) - Wu, Lijuan; Lei, Bing; Yang, Hang; Song, Yue; Zhang, Yinyan
Abstract: A 4H-SiC Junction Barrier Schottky Diode with Segregated Floating Trench and Super Junction (S-FT SJ JBS) is presented in this paper. By adopting segregated integrated trench and super junction, the high electric field not only focus on the bottom of trench but also gathers in the top of trench and the edge of super junction, therefore the distributions of the high electric field is more uniform, and thus to substantially improve the breakdown voltage (BV). By using the floating trench, the area of schottky contact is enlarged, thus the density of current is increased in the on state, and the specific on-resistance ( R on, sp ) of the device is ultimately decreased. The results of simulation show that the BV and R on, sp of S-FT SJ JBS diode are 1891V and 0.16 mΩ cm 2, and the BV is improved by 29.5% and the R on, sp is decreased by 50% compared with I-FT SJ JBS diode. The Baliga figure-of-merit (BFOM) of S-FT SJ JBS diode is 894 W·cm −2 which is increased by 236.1% compared with I-FT SJ JBS diode. Highlights: Wide band gap semiconductor materials represented by 4H-SiC shows a prospect on designing of power device. Floating trench is used to forming MIS structure which withstands a part of voltage drop. Floating trench increases the area of schottky contact, which reduces the specific on-resistance substantially. Super junction is used to keep charge balance. Structure of segregated floating trench and super junction uniforms the distributions of electric field. The diode we designed breaks the 4H-SiC Unipolar Limit.